Structure of an invertebrate gene encoding cytoplasmic intermediate filament (IF) proteins: implications for the origin and the diversification of IF proteins. - Dodemont, H (1990)
The structure of the single gene encoding the cytoplasmic intermediate filament (IF) proteins in non-neuronal cells of the gastropod Helix aspersa is described. Genomic and cDNA sequences show that the gene is composed of 10 introns and 11 exons, spanning greater than 60 kb of DNA. Alternative RNA processing accounts for two mRNA families which encode two IF proteins differing only in their C-terminal sequence. The intron/exon organization of the Helix rod domain is identical to that of the vertebrate type III IF genes in spite of low overall protein sequence homology and the presence of an additional 42 residues in coil 1b of the invertebrate sequence. Intron position homology extends to the entire coding sequence comprising both the rod and tail domains when the invertebrate IF gene is compared with the nuclear lamin LIII gene of Xenopus laevis presented in the accompanying report of Döring and Stick. In contrast the intron patterns of the tail domains of the invertebrate IF and the lamin genes differ from those of the vertebrate type III genes. The combined data are in line with an evolutionary descent of cytoplasmic IF proteins from a nuclear lamin-like progenitor and suggest a mechanism for this derivation. The unique position of intron 7 in the Helix IF gene indicates that the archetype IF gene arose by the elimination of the nuclear localization sequence due to the recruitment of a novel splice site. The presumptive structural organization of the archetype IF gene allows predictions with respect to the later diversification of metazoan IF genes. Whereas models proposing a direct derivation of neurofilament genes seem unlikely, the earlier speculation of an mRNA transposition mechanism is compatible with current results.